2014
DOI: 10.1007/s00216-014-7676-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of 21 metabolites of methylnaphthalenes and polycyclic aromatic hydrocarbons in human urine

Abstract: Polycyclic aromatic hydrocarbons (PAHs) and their alkylated derivatives, such as methylnaphthalenes (MeNs), are harmful pollutants ubiquitously present in the environment. Exposure to PAHs has been linked to a variety of adverse health effects and outcomes, including cancer. Alkyl PAHs have been proposed as petrogenic source indicators because of their relatively high abundance in unburned petroleum products. We report a method to quantify 11 urinary methyl naphthols (Me-OHNs), metabolites of 1- and 2-methylna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…With SRMs 3672 and 3673 being the first reference materials characterized for OH-PAHs, they will be useful in future studies to verify the methods used. In a study recently published by CDC, Li et al [27] used SRMs 3672 and 3673 to validate a new GC-MS/MS method for quantifying 21 metabolites of methylnapthalenes and PAHs in human urine. In the development of the method, they confirmed the certified values for the OH-PAHs [27].…”
Section: Resultsmentioning
confidence: 99%
“…With SRMs 3672 and 3673 being the first reference materials characterized for OH-PAHs, they will be useful in future studies to verify the methods used. In a study recently published by CDC, Li et al [27] used SRMs 3672 and 3673 to validate a new GC-MS/MS method for quantifying 21 metabolites of methylnapthalenes and PAHs in human urine. In the development of the method, they confirmed the certified values for the OH-PAHs [27].…”
Section: Resultsmentioning
confidence: 99%
“…We measured urinary SCN using ion chromatography coupled with ESI-MS/MS with a LOD of 20 ng/mL (Blount and Valentin-Blasini, 2006; Valentín-Blasini et al, 2007). We measured urinary OH-PAHs using isotope-dilution gas chromatography (GC) coupled with MS or MS/MS with LODs in the range of 1.0–19 picograms per milliliter (pg/mL) (Li et al, 2006, 2014). We measured sCOT using HPLC coupled with atmospheric ionization (API)–MS/MS with a LOD of 0.015 ng/mL for all NHANES participants (Bernert et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…While many epidemiological studies have demonstrated that long-term exposure to traffic-related air pollution (e.g., particulate matter less than 2.5 µm (PM 2.5 ) and polycyclic aromatic hydrocarbons (PAH)) were associated with the increased risk of developing asthma and asthma-related symptoms in children (Gehring et al 2010; Jung et al 2012; McConnell et al 2010), it is less clear whether traffic-related air pollutants contribute to the development of allergic sensitization given inconsistent results. For example, while few studies reported positive associations between long-term exposure to outdoor traffic-related air pollution (e.g., PM 2.5 , PM 2.5 absorbance and NO x ) and allergic sensitization to outdoor allergens (i.e., pollen) (Morgenstern et al 2008; Nordling et al 2008), a meta-analysis on five European Birth prospective cohort studies (i.e., BAMSE-Sweden, LISAplus and GINIplus-Germany, MASS-Great Britain, and PIAMA-The Netherlands) indicated that the long-term exposure to those air pollutants was not associated with the development of allergic sensitization in children (Gruzieva et al 2013).…”
Section: Introductionmentioning
confidence: 99%